1991
DOI: 10.1677/joe.0.1280253
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and autoradiographical localization of oxytocin receptors within the ovine endometrium in relation to post-partum corpus luteum function

Abstract: The induction of ovulation in early post-partum ewes is associated with a high incidence of premature luteal regression which is independent of the suckling stimulus but dependent on the stage post partum. The aim of the present study was to determine whether oxytocin receptors are present on uterine endometrium early in the luteal phase and hence ascertain whether oxytocin-induced uterine prostaglandin F2 alpha release is a possible mechanism involved in the premature regression of these post-partum corpora l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
1
2
1
Order By: Relevance
“…The localization of oxytocin binding sites and the s ecificity of the labellin in the myometrium and on shown in this study is in full agreement with autoradiographical studies in ovine uterus (Ayad et al, 1991;Wallace et al, 1991a,b). However, whereas Wallace et al (1991b) reported labelling of the outer layer of the myometrium, we found labelling in both the circular and the longitudinal muscle layers. Moreover, the high resolution of the tritiated radioligand used in our study demonstrated that the labelled epithelial cells in the rat are of the simple columnar type and that cells of the deeper lying glands, which are continuous with the surface epithelium, are also labelled.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The localization of oxytocin binding sites and the s ecificity of the labellin in the myometrium and on shown in this study is in full agreement with autoradiographical studies in ovine uterus (Ayad et al, 1991;Wallace et al, 1991a,b). However, whereas Wallace et al (1991b) reported labelling of the outer layer of the myometrium, we found labelling in both the circular and the longitudinal muscle layers. Moreover, the high resolution of the tritiated radioligand used in our study demonstrated that the labelled epithelial cells in the rat are of the simple columnar type and that cells of the deeper lying glands, which are continuous with the surface epithelium, are also labelled.…”
Section: Discussioncontrasting
confidence: 97%
“…The binding of oxytocin to myometrial tissue is abruptly increased a t parturition (Riemer et al, 1986) and plays an important role in the delivery of the fetus. In addition, at estrus, increased binding in the endometrium of the ewe was reported by means of binding assays (Roberts et al, 1976) and autoradiography (Wallace et al, 1991b). Roberts and coworkers (1976) also reported a decrease in oxytocin receptor concentration during the postovulatory phase of the estrous cycle.…”
mentioning
confidence: 96%
“…Ayad, Guldenaar & Wathes (1991) and Wallace, Morgan, Helliwell et al (1991) reached the same conclusion with regard to binding sites for oxytocin being present in the uterus and oviduct of the ewe. In the present study, l25I-labelled OTA used at a low concentration labelled oxytocin-binding sites in the reproductive tract of the female guinea-pig.…”
supporting
confidence: 59%
“…On the other hand, the OT binding sites have been localized only in the outer longitudinal smooth muscle layer in the ovine myometrium (46,47). OT seems to be unable to induce spontaneous contractions in isolated muscle sections from the inner myometrium layer of nonpregnant and of postpartum uteri (24).…”
Section: Myometriummentioning
confidence: 99%